S66 Caffeine Inhibits TGFβ Activation by Epithelial Cells, Interrupts Fibroblast Responses to TGFβ, and Reduces Pulmonary Fibrosis in Ex Vivo Precision-cut Lung Slices. (12th November 2015) - Tatler, AL; Barnes, J; Habgood, A; Goodwin, A; McAnulty, R; Jenkins, RG
Abstract : Caffeine (1, 3, 7-tri-methylxanthine) is a common food additive found naturally in many products. It is a non-selective competitive antagonist of G-protein coupled adenosine receptors and can inhibit phosphodiesterases. Caffeine has anti-fibrotic effects in the liver and increased caffeine consumption has been associated with reduced liver fibrosis in patients with chronic hepatitis C infection. The effect of caffeine on pulmonary fibrosis has not been investigated, however, it has been shown to inhibit TGFβ-induced Smad signalling in epithelial cells. This study aimed to investigate the anti-fibrotic effects of caffeine in the lung using lung epithelial cells, fibroblasts and an ex vivo precision-cut lung slice (PCLS) model of fibrosis. Immortalised human bronchial epithelial cells (iHBECs) and primary human lung fibroblasts from were used. TGFβ activation was assessed using an in vitro TGFβ reporter cell assay and assessment of phosphorylated Smad2. Expression of pro-fibrotic genes was assessed by quantitative polymerase chain reaction. Proliferation of fibroblasts was assessed by brdU incorporation assay. Finally, the effect of caffeine on established lung fibrosis was investigated ex vivo using PCLS. Mice were instilled with saline or 60 IU bleomycin and PCLS obtained after 28 days. PCLS were treated with increasing concentrations of caffeine for five days prior to measurement of collagen by high-performance liquid chromatography. Viability of the PCLS following caffeine treatment was assessed by MTT assay. Caffeine induced a concentration-dependent decrease in TGFβ activation in iHBECs but had no effect on TGFβ activation in lung fibroblasts. Furthermore, caffeine reduced expression of the TGFβ-inducible genes PAI1 and Col1A and reduced TGFB1 transcript in epithelial cells. Additionally, caffeine reduced TGFβ-induced proliferation of lung fibroblasts and reduced expression of pro-fibrotic genes including COL1A and ACTA2 . Crucially, ex vivo treatment of fibrotic PCLS from bleomycin treated animals with caffeine caused a dose-dependent reduction in collagen deposition after five days. Caffeine had no effect on collagen deposition in PCLS isolated from saline treated animals nor did caffeine affect tissue viability in PCLS from either saline or bleomycin treated animals. In conclusion, caffeine has anti-fibrotic effects in the lung via concomitant inhibition of epithelial TGF activation and fibroblast responses to TGFb.